Cancer cells induce immune escape via glycocalyx changes controlled by the telomeric protein TRF2. (18th April 2019) - Cherfils‐Vicini, Julien; Iltis, Charlene; Cervera, Ludovic; Pisano, Sabrina; Croce, Olivier; Sadouni, Nori; Győrffy, Balázs; Collet, Romy; Renault, Valérie M; Rey‐Millet, Martin; Leonetti, Carlo; Zizza, Pasquale; et al.
Abstract: Myeloid‐derived suppressor cells (MDSCs) are immature myeloid cells with strong immunosuppressive activity that promote tumor growth. In this study, we describe a mechanism by which cancer cells control MDSCs in human cancers by upregulating TRF2, a protein required for telomere stability. Specifically, we showed that the TRF2 upregulation in cancer cells has extratelomeric roles in activating the expression of a network of genes involved in the biosynthesis of heparan sulfate proteoglycan, leading to profound changes in glycocalyx length and stiffness, as revealed by atomic force microscopy. This TRF2‐dependent regulation facilitated the recruitment of MDSCs, their activation via the TLR2/MyD88/IL‐6/STAT3 pathway leading to the inhibition of natural killer recruitment and cytotoxicity, and ultimately tumor progression and metastasis. The clinical relevance of these findings is supported by our analysis of cancer cohorts, which showed a correlation between high TRF2 expression and MDSC infiltration, which was inversely correlated with overall patient survival. Synopsis: How tumors instruct an immunosuppressive microenvironment is currently unclear. Here, the telomere protein TRF2 is shown to exert extratelomeric roles in cancer cells altering the glycocalyx gene expression, resulting in recruitment of myeloid‐derived suppressor cells (MDSC). These results suggest TRF2 as a valuable target for future immunotherapies. Increased TRF2 expression in cancer cells favors tumorigenesis and metastasis in mouse models in vivo . Elevated TRF2 promotes MDSC recruitment and activation via the TLR2/MyD88 pathway, blunting natural killer cell immunosurveillance. TRF2 controls MDSCs through transcriptional activation of heparan sulfate proteoglycan biosynthesis genes HS3ST4, GPC6, and VCAN. TRF2 upregulation in human malignancies is associated with MDSC infiltration and high expression of glycocalyx genes. Abstract : TRF2 has extratelomeric roles enabling tumor cells to adjust their glycocalyx and to attract immunosuppressive immature myeloid cells.